Mathematical Models of Combustion Processes - Denisov, I. V.; Denisov, A. I. (Journal of mathematical sciences (New York, N.Y.), 2024)
In this paper, we consider model problems of chemical kinetics that lead to singularly perturbed parabolic equations in domains with nonsmooth boundaries. The solvability of such problems depends on the properties of the inhomogeneity at corner points of the boundary.